Terrorism Shocks and Stock Market Reaction Patterns - Christos Kallandranis; Konstantinos Drakos (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this Policy Briefing, we discuss two important questions: (i) whether and how terrorism shocks are transmitted across international stock markets, (ii) what is the role of behavioral factors in explaining these stock market reactions. According to our findings terrorism shocks are indeed diffused cross-nationally in a non-uniform manner. Economic channels such as the degree of a country's integration with the world market, its liquidity and its ties to the zeroground country are found to play an important role. Additionally, we document that the likelihood and the size of a negative stock market reaction increase with a country's terrorism record and terrorism risk concern, as well as the psychosocial impact caused by the terrorism incident.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330